Differentiated osteoblasts derived decellularized extracellular matrix to promote osteogenic differentiation - Jin Jeon; Min Suk Lee; Hee Seok Yang (Biomaterials Research, 2018)
Abstract Background The extracellular matrix (ECM) can directly or indirectly influence on regulation of cell functions such as cell adhesion, migration, proliferation and differentiation. The cell derived ECM (CD-ECM) is a useful in vitro model for studying the comprehensive functions of CD-ECM because it maintains a native-like structure and composition. In this study, the CD-ECM is obtained and a test is carried out to determine the effectiveness of several combinations of decellularized methods. These methods were used to regulate the optimal ECM compositions to be induced by osteogenic differentiation using primary isolated osteoblasts. Result We investigated the effect of osteoblasts re-seeded onto normal osteoblast ECM under the growth medium (GM-ECM) and the osteogenic differentiation medium (OD-ECM). The osteoblasts were then cultured statically for 1, 2, and 4 weeks in a growth medium or differentiation medium. Before osteoblast culture, we performed immunostaining with filamentous actin and nuclei, and then performed DNA quantification. After each culture period, the osteogenic differentiation of the osteoblasts re-seeded on the OD-ECMs was enhanced osteogenic differentiation which confirmed by alkaline phosphatase staining and quantification, Alizarin Red S staining and quantification, and von Kossa staining. The OD-ECM-4 W group showed more effective osteogenic differentiation than GM-ECM and OD-ECM-2 W. Conclusions The OD-ECM-4 W has a better capacity in a microenvironment that supports osteogenic differentiation on the GM-ECM and OD-ECM-2 W. The ECM substrate has a wide range of applications as cell culture system or direct differentiation of stem cell and excellent potential as cell-based tissue repair in orthopedic tissue engineering.